Qualitative study of influences on food store choice - Krukowski, Rebecca A. (2012)
Previous research indicates food store choice influences dietary intake and may contribute to health disparities. However, there is limited knowledge about the reasons which prompt the choice of a primary food store, particularly among populations vulnerable to obesity and chronic diseases (e.g., individuals living in rural locations and African-Americans). Purposive sampling was used to select rural and urban communities (3 African-American and 2 Caucasian focus groups; n=48) in Arkansas from June to November 2010, allowing examination of potential racial or rurality differences. Primary household food shoppers (n=48) (96% female, 63% African-American, mean age=48.1±13.9 years old, mean BMI=30.5±7.8) discussed reasons for choosing their primary store. Qualitative analysis techniques—content analysis and constant comparison—were used to identify themes. Four themes emerged: proximity to home or work, financial considerations and strategies, availability/quality of fruits, vegetables, and meat, and store characteristics (e.g., safety, cleanliness/smell, customer service, nonfood merchandise availability, and brand availability). While there were persistent rurality differences, the relevant factors were similar between African-American and Caucasian participants. These findings have important implications for future policies and programs promoting environmental changes related to dietary intake and obesity, particularly in rural areas that appear to have significant challenges in food store choice.